2023
DOI: 10.3847/1538-4357/acbf33
|View full text |Cite
|
Sign up to set email alerts
|

The Polytropic Behavior of Solar Wind Protons as Observed by the Ulysses Spacecraft during Solar Minimum

Abstract: We analyze proton bulk parameters derived from Ulysses observations and investigate the polytropic behavior of solar wind protons over a wide range of heliocentric distances and latitudes. The large-scale variations of the proton density and temperature over heliocentric distance indicate that plasma protons are governed by subadiabatic processes (polytropic index γ < 5/3), if we assume protons with three effective kinetic degrees of freedom. From the correlation between the small-scale variations of the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 44 publications
4
16
0
Order By: Relevance
“…We derive the radial transportation of the value of kappa of the solar wind plasma protons in the heliosphere from R = 1 up to R = 100 au. We consider two radial profiles for the polytropic index, (a) a constantly adiabatic expansion of plasma protons that corresponds to a fixed polytropic index of γ = 5/3 (e.g., Kartalev et al 2006;Nicolaou et al 2014;Livadiotis & Desai 2016;Nicolaou et al 2023), and (b) the sub-adiabatic expansion with a polytropic index γ(R) that follows the model in Equation ( 22). Figure 3 (upper panels) shows these two cases of polytropic index radial profile throughout the heliosphere.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We derive the radial transportation of the value of kappa of the solar wind plasma protons in the heliosphere from R = 1 up to R = 100 au. We consider two radial profiles for the polytropic index, (a) a constantly adiabatic expansion of plasma protons that corresponds to a fixed polytropic index of γ = 5/3 (e.g., Kartalev et al 2006;Nicolaou et al 2014;Livadiotis & Desai 2016;Nicolaou et al 2023), and (b) the sub-adiabatic expansion with a polytropic index γ(R) that follows the model in Equation ( 22). Figure 3 (upper panels) shows these two cases of polytropic index radial profile throughout the heliosphere.…”
Section: Resultsmentioning
confidence: 99%
“…The solar wind flows radially outward from the Sun and expands in the inner heliosphere (heliocentric distance R less than ∼ 10 au) in an almostadiabatic cooling (γ ∼ 1.4-1.6, e.g., see Livadiotis & Desai 2016;Nicolaou et al 2023), namely, the flowing solar wind plasma expands in the heliosphere without significant energy exchange (negligible heating rate). However, both observations and existing models agree that the polytropic index further out from the heliosphere differs significantly from being adiabatic.…”
Section: Polytropic Indexmentioning
confidence: 99%
“…Equation 47b is fitted to the three observations shown in Figure 3(b), that is, γ ∼ 1.6 near R ∼ 1 au, using Wind data (Livadiotis & Desai 2016), γ ∼ 1.4 near R ∼ 5 au, using Ulysses data (Nicolaou et al 2023), and γ ∼ 1 near R ∼ 30 au, using New Horizons data (Elliott et al 2019). The above example is simplified and only included solar wind protons, excluding both pickup ions and electrons, or in general, the multi-particle description.…”
Section: Example: Application In the Inner Heliospherementioning
confidence: 99%
“…The heating of the solar wind increases with heliocentric distance, becoming more significant in the outer heliosphere, and thus solar wind thermodynamics is described by nonadiabatic processes, especially in the outer heliosphere. Indeed, while near adiabatic processes are observed within a few au of the Sun (e.g., Livadiotis & Desai 2016, near 1 au; Nicolaou et al 2023, up to 5 au), nonadiabatic processes are increasingly observed in the outer heliosphere (Elliott et al 2019). If the plasma expansion was exactly adiabatic, the temperature would be much lower than the observations revealed; this is because nonadiabatic temperatures have higher values than they would have been under an adiabatic cooling, indicating the presence of significant heating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation